Study protocol: a randomized controlled clinical trial on the use of electroacupuncture for postoperative abdominal distension following laparoscopic cholecystectomy - Kong, Qi; Wang, Wei; Chen, Xin-Yi; Chen, Li-Ming; Sun, Long-Kai; Qu, Shao-Hua; Wu, Wen-Tao; Yang, Jia-Hua; Shu, Yu; Li, Sen; Yin, Pei-Hao; Li, Wei (Frontiers in Surgery, 2025)
BackgroundIn recent years, global cholecyst-related disorders have been increasing daily. Laparoscopic cholecystectomy (LC) is an advanced gallbladder surgical technique. However, pneumoperitoneum and various factors leading to abdominal distension and other gastrointestinal dysfunctions are common postoperative complications. Although postoperative gastrointestinal dysfunction can be treated with Avimopan, this medication also has adverse reactions such as nausea and vomiting. Acupuncture is one of the distinct treatment methods in TCM (Traditional Chinese Medicine), characterized by its simplicity, practicability, and minimal side effects. Previous studies have confirmed the effectiveness of acupuncture intervention for gastrointestinal functionality.MethodThis study is a randomized, single-blind, controlled pilot clinical trial. We divided the patients into two groups: Electroacupuncture (EA) meridian acupoint group and EA non-meridian non-acupoint group. During the study period, both groups will receive routine care and education with an anticipated total of 36 individuals in each group. Both groups of patients will be treated with electroacupuncture (EA) after surgery, and in the morning of the day following the operation, with each session lasting 30 min. Specifically, the EA meridian acupoint group had intervention at the bilateral Zusanli (ST36) and Neiguan (PC6) points, while the EA non-meridian non-acupoints group had selected acupoint interventions at about 1.5 cm from ST36 and PC6. We will use the VAS (Visual Analogue Scale) and abdominal distension grading to evaluate the degree of patients’ postoperative abdominal distension 1–6 h and 24 h after surgery to obtain outcome assessments.Expected outcomeThis study aims to scientifically and standardly evaluate the impact of EA in lessening post-LC abdominal distension through a clinical trial. We hope to get direct clinical evidence to demonstrate the role that EA can play in the ERAS (enhanced recovery after surgery) in patients post-LC. We hypothesise that the therapeutic effect of EA at meridian acupoints is superior to EA at non-meridian non-acupoint in the comprehensive intervention after LC.Clinical Trial Registrationhttp://www.chictr.org.cn, identifier ChiCTR2300073134.